La estimulación musical para el desarrollo del lenguaje de las niñas y niños de 2 a 3 años de inicial I en el salón azul del Centro de Desarrollo Infantil Universitario de la ciudad de Loja, parroquia San Sebastián. Periodo 2014 - 2015 - Yanza Macas, Celmira Natividad (2016)
This paper "The musical stimulation for language development of children from 2-3 years of initial I in the Blue Room of the Child Development Center of the City University of Loja, San Sebastian Parish. Period 2014 - 2015 ", has the general objective to contribute to the development of language through music stimulation of children from 2-3 years by using research methods such as scientific, statistical and Synthetic analytical; and the instrument used was the test of IDL and was applied to children. The population sample was present were 17 children. The results obtained in the application of the instruments found that the diagnosis was found that 11 children representing 65% have no problem with the language and develop it in a proper way, while 6 children and girls represent 35% have difficulty understanding and perform tasks given by teachers. Therefore it concludes that children need to develop a musical adaptation language. As recommended that fits into the curriculum to music as a method of language development.